An approach to moral motivation in verses and narratives from the perspective of religious ethics psychology - Javad Ghaffari; Behrouz Mohammadi Monfared; Vahid Vahed Javan; Ali Asgari Yazdi (اخلاق وحیانی)
Humans in their nature and innately have the motivation to perform moral behavior. But why do people not have the motivation to behave morally in some situations? Or even have the motivation to behave immorally. They become careless and evil. The same problem exists in the moral teachings of religion. The main question of the article is, "Why do religious people or those who claim to be religious, knowing the moral requirements of religion, do not have the motivation to perform moral actions?". Or sometimes they act against the moral orders of religion. So what is the relationship between religious beliefs aimed at moral propositions and moral motivation? Since the concept of "motivation" and related theories are discussed in "psychology" and the concept of "moral motivation" is one of the important and key topics in "moral psychology". For this reason, this article with a descriptive and analytical method tries to explain the factors and obstacles of "moral motivation" from a new perspective called "psychology of religious ethics" by referring to some verses and narrations. The result is that internal factors such as "weakness of will", "Faith" and "irreligiousness" and overcoming "desires and instincts" and "lack of awareness" and carelessness are obstacles to moral motivation. Also, external factors such as family, education and training system of society, real and virtual social relations and government behavior are effective in moral motivation of people.